Estudio comparado de las estimaciones de dos versiones de Modelo de Aceptación de la Tecnología (TAM) mediante los programas amos y PLS - L. M. López Bonilla; J. M. López Bonilla (Investigaciones Europeas de Dirección y Economía de la Empresa (IEDEE), 2006)
In this paper we carry out a comparison among two versions of the model of acceptance of the technology, generally known by its acronyms TAM, by means of the utilization of two differentestimation procedures families inside the methodology of the structural equations: the structures of covarianzas and the analysis of the partial least square. In representation of these methods we have elected the data processing programs AMOS and PLS, respectively. The results obtained indicate substantial differences among both procedures, so much in the analyses of the models of measure as in that of the structural models.
Keywords: 330; TAM; adoption of innovations; acceptance of the tecnology; adoption processes; estructures of covariances and variances